Beneath the deadly nuclear clouds - Abd Razak, Dzulkifli (1995)
IN MARCH 1970, IT SEEMED THE world was resolved not to let history repeat itself when the Nonproliferation of Nuclear Weapons Treaty (NPT) was endorsed under the auspices of the United Nations. The Treaty said to be the most multilateral treaty after the United Nations Charter, was designed to prevent the spread of nuclear weapons and to further the goal of general and complete disarmament. For example Article VI in the Treaty states: "Each of the Parties to the Treaty undertakes to pursue negotiations in good faith on effective measures relating to the cessation of the nuclear arms race at an early date and to nuclear disarmament, and on a treaty on general and complete disarmament under strict and effective international control." For this purpose, NPT is given a life span of 25 years by which time the negotiations for nuclear disarmament was expected to be completed.